Brûler les champs, pour voir ensuite ce qui va repousser - Pitre, Éléonore; Holder, Frannie (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Presented here in conversation, guitarists Frannie Holder (Dear Criminals, Random Recipe) and Éléonore Pitre (Rosier, Star Académie house band) discuss the pandemic as a moment to reflect on their lives as musicians and to focus more on the “why” of their work. Both musicians also describe the singular experience of performing in person during the pandemic.